THE EFFECTIVENESS OF THE DRILL METHOD IN IMPROVING THE ARABIC SPEAKING SKILLS OF EIGHTH-GRADE STUDENTS AT MTS ASSALAM BANGILAN TUBAN - Ifa Ulfiana Mayla Rosyda; Azwar Annas (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2026)
This study aims to determine the initial speaking skill proficiency of eighth-grade students at MTs Assalam Bangilan Tuban and to examine the effectiveness of the drill method in improving these skills. This study used a quantitative approach with a quasi-experimental design in the form of a one-group pretest-posttest design. The sample consisted of 26 students studying at MTs Assalam Bangilan Tuban. Data were collected through oral tests covering aspects of pronunciation, fluency, sentence structure, vocabulary mastery, and self-confidence. Data analysis was conducted using descriptive statistics and the Shapiro–Wilk normality test. Since one of the datasets was not normally distributed, hypothesis testing was carried out using the Wilcoxon test. The results showed that the students’ mean score increased from 36.15 in the pretest to 52.15 in the posttest. In addition, the Wilcoxon test obtained a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. These findings indicate that the drill method was effective in improving students’ Arabic speaking skills.